ANALISIS KUALITAS AIR MINUM DAN KANDUNGAN LOGAM BERAT TIMBAL (Pb) PADA DEPOT AIR MINUM ISI ULANG (DAMIU) DI KOTA PALANGKA RAYA-KALIMATAN TENGAH - Dwi Hermayantiningsih; Muh. Supwatul Hakim; Tety Wahyuningsih Manurung (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
An analysis of drinking water quality, including physical parameters such as TDS (Total Dissolved Solids), color, odor, and taste, as well as chemical parameters such as pH and lead ion content in refillable drinking water depots in Palangka Raya City, has been conducted. Drinking water requirements must comply with the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023 concerning the Implementation of Government Regulation Number 66 of 2014 regarding Environmental Health. The method throughout this investigation is laboratory experiment. Samples of refillable drinking water were obtained using a random sampling method at 9 different locations in Jekan Raya District. Based on the analysis of physical parameters including TDS, color, odor, and taste, the drinking water sample still meets drinking water quality standards. The results of pH measurements at 7 out of 9 sampling points showed that the pH values of 6.5-8.5 did not meet the quality standards. Analysis of lead (Pb) levels based on AAS showed that the Pb content in 9 samples was below the maximum permissible standard of 0.01 mg/L.